FIRE CANNOT KILL A DRAGON : GAME OF THRONES AND THE OFFICIAL UNTOLD STORY OF THE EPIC SERIES - Hibberd, James (UK : Bantam Press, 2020)
Game of Thrones is the biggest television drama ever to have graced our screens. The epic saga of warring families, huge battles, arduous journeys and dying heroes has captured the hearts and attention of millions of fans across the world. But its conclusion isn't necessarily the end of the story... Here, James Hibberd chronicles the untold story of Game of Thrones, from the creative team's first meetings to staging the series finale, including the on-camera battles and off-camera struggles that became legends of their own. The stories shared are rich and surprising and reveal deeper insights into storylines that continue to fascinate, such as what it was like for Kit Harington to pretend Jon Snow was dead for two years. With more than fifty new interviews, rare and stunning photos, and unprecedented access to the cast, crew and producers, this is a celebration of an unforgettable time in television history.
Includes index.
Keywords: Game of thrones (Television program); Fantasy television programs -- Production and direction